Music Performance Policy during Covid-19 Crisis: Expectations Versus Reality - Hidayatullah, Riyan (LPPM Universitas Lampung, 2021)
This paper examines public discourse on web pages and social media as a form of digital ethnography during the COVID-19 crisis. During the